URGENSI MODEL DISCOVERY LEARNING DALAM PEMBELAJARAN IPS DI SEKOLAH DASAR - Oktaviani Anggut; Rudolof Ngalu; Alfonsus Sam (Jurnal Literasi Pendidikan Dasar (JLPD), 2021)
The problem in this research was the low social studies learning outcomes of elementary school students. This because the teacher emphasizes more on teacher centered strategies in the learning process, The students only as listeners. The methods and models used by the teacher are not pleasant such as the use of the lecture method, and the text book learning. The purpose of this study was to explain the urgency of the discovery learning model in social studies learning in elementary schools. This type of research was library research. The data sources used in this study were secondary data such as textbooks and the results of previous studies in the form of articles and theses. Data collection techniques in this study were carried out by tracing and reviewing various literatures related to this research. The results of this study indicated that the discovery learning model be is very urgent to be applied in the elementary social studies learning process. This was because the discovery learning model can greatly improve the results of learning science social for both teachers and students for, is able to provide ideal guarantees for student maturity so that it can strengthen studentes’ insight and can motivate students to be actively involved in learning